Association between body mass index and mortality in a prospective cohort of Chinese adults. Issue 32 (August 2016) - Sun, Hao; Ren, Xiaoxia; Chen, Zhichao; Li, Chunsheng; Chen, Shuohua; Wu, Shouling; Chen, Youren; Yang, Xinchun
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Obesity is associated with an increased risk of diabetes mellitus, hypertension, and coronary artery disease; however, the relation between body mass index (BMI) and the risk of all-cause mortality is controversial. We prospectively examined the relationship between BMI and all-cause mortality in 123, 384 Chinese men and women who participated in the Kailuan health examination study from 2006 to 2007 and 2008 to 2009. Cases included 6218 deaths (5770 men and 448 women) that occurred during a mean follow-up period of 7.39 years. Relative risk was adjusted for factors such as age, serum lipid levels (ie, triglyceride, high-density lipoprotein, and low-density lipoprotein cholesterol), history of smoking and drinking, and physical activity, as well as a medical history of hypertension, diabetes, myocardial infarction, and stroke. Within the cohort, the lowest risk of all-cause mortality was seen among persons with a BMI of 24 to 28 kg/m 2 in male, and the risk was elevated among persons with BMI levels lower or higher than that range. Moreover, all-cause mortality was greatest in the group with a BMI of <18.5 kg/m 2 . In contrast, in female, a high BMI was associated with increased mortality, and a BMI of <18.5 kg/m 2 was associated with the lowest risk. Further, a U-shaped association was seen between BMI and the risk of death from any cause among men and women, even after adjusting for confounding factors. In conclusion, underweight was associated with a substantially increased risk of all-cause mortality in males. The excess risk of all-cause mortality with a high BMI, however, was seen among females.